Effects of Cement Treatment on Water Retention Behavior and Collapse Potential of Gypseous Soils: Experimental Investigation and Prediction Models - Hussein Q. Abdulameer AlNaddaf; Saeed Kouzegaran; Mohammed Y. Fattah; Ali Akhtarpour (Advances in Civil Engineering)
Gypseous soil poses a significant challenge in geotechnical engineering due to its susceptibility to collapse under saturation. This type of soil covers approximately 33% of regions in Iraq, primarily in unsaturated conditions. This study focuses on two types of gypseous soils: one with moderate gypsum content from Karbala city (G1) and the other with high-gypsum content from Tikrit city (G2), to investigate the effects of cement treatment on their water retention behavior and potential for reducing collapse. Different percentages of cement were mixed with both soils to determine the optimum soil–cement mixture for reducing collapse potential (CP) through single oedometer tests. The water retention characteristics and water retention behavior of samples with varying gypsum content and different levels of cement treatment were examined and compared using a controlled-suction oedometer. The soil–water retention curve (SWRC) of these natural and treated gypseous soils was also investigated and compared in both wetting and drying paths. Additionally, multiple pedotransfer functions (PTFs) were assessed to identify or adapt prediction equation(s) for the SWRC of gypseous soil both with and without cement treatment with acceptable accuracy. The results show that adding cement can decrease the CP of gypseous soils; it also affects their SWRC significantly. By making some simple modifications, the PTFs demonstrate acceptable estimations for the water retention curve of both natural and cement-treated gypseous soils.